Human factors multi-technique approach to teenage engagement in digital technologies health research - Lang, Alexandra R.; Craven, Michael P.; Atkinson, Sarah; Simons, Lucy; Cobb, Sue; Mazzola, Marco (Springer International Publishing Switzerland, 2016)
This chapter explores the use of multi-techniques for teenage HCI health research. Through four case studies we present information about adolescents as users of healthcare services and technologies, adolescent personal development and the human factors approaches through which teenagers have been involved in healthcare research projects. In each case study; comprising of the design or evaluation of a new digital technology for supporting health or well-being, the techniques used by researchers to involve teenagers are explored and analysed. The case studies examine various aspects of technology design and use including but not limited to usability, acceptability and learnability. The penultimate section of the chapter presents a ‘Schema for Multi-technique HCI Health Research with Teenagers’ and provides the supporting case for a multi method approach. The conclusions of the chapter reinforce the benefits that are specific to the implementation of multi-technique research with teenager participants. Consideration of the eight factors outlined in the ‘Schema’ within study designs should serve to unlock the potential of teenagers, ensuring reliable elicitation of their views and needs.